PENINGKATAN HASIL BELAJAR MELALUI MEDIA DIORAMA PADA MATERI WUJUD ZAT DAN PERUBAHANNYA KELAS IV SDN SIRAPAN 02 KABUPATEN MADIUN - Dyestia Avarini Viardatiwi; Yudi Hartono; Karni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to improve the learning outcomes of class IV students at SDN Sirapan 02 Madiun Regency on the material of forms of matter and their changes using diorama media. The method used is classroom action research (PTK) with the spiral model from Kemmis and McTaggart which consists of four stages: planning, implementation, observation and reflection, which is carried out in a pre-cycle and two cycles. The research subjects were 16 class IV students. Data collection was carried out through learning results tests, observation, interviews and documentation, analyzed descriptively qualitatively and quantitatively. The results showed an increase in the average score from 65.7 in cycle I to 82.3 in cycle II, as well as an increase in student motivation and enthusiasm. Diorama media is effective in improving learning outcomes and can be used as an interactive learning medium for science material.